Coalitions, coordination, and contestation: a systematic review of the advocacy coalition framework and its implications for sustainability transitions research - Wesche, Julius P.; Dütschke, Elisabeth; Negro, Simona O.; Hekkert, Marko P. (Frontiers in Political Science, 2025)
IntroductionAchieving sustainability transitions requires substantial policy changes, often driven by coalitions of actors advocating for institutional change and transformative agendas. While the transitions literature highlights the importance of coalition coordination, the underlying processes remain insufficiently understood. This study explores the Advocacy Coalition Framework (ACF) to derive insights into the coordination and dynamics of advocacy coalitions relevant to sustainability transitions.MethodsA systematic review of ACF literature was conducted, encompassing an initial corpus of over 700 articles and refining it to a final set of 45 documents. These documents were analyzed using qualitative coding to identify key factors influencing coalition coordination and to conceptualize coalition dynamics across the phases of sustainability transitions.ResultsThe review identifies four categories of factors shaping coalition coordination: prerequisites for coordination, reasons to coordinate, instrumental factors that influence coordination, and internal organization of coalitions. Additionally, it outlines how coordination patterns evolve across four sustainability transition phases, leading to the development of a typology that integrates dynamics within coalitions and across coalitions with two transition pathways: technological substitution and reconfiguration.DiscussionThis study advances the understanding of the political processes underpinning sustainability transitions by integrating ACF insights into transition studies. It underscores the importance of belief systems, resource access, and trust in fostering effective coalition coordination. The proposed typology offers a conceptual framework to guide future empirical research on coalition dynamics and their role in accelerating sustainability transitions.